2015
DOI: 10.1038/ncomms7253
|View full text |Cite
|
Sign up to set email alerts
|

Roquin binds microRNA-146a and Argonaute2 to regulate microRNA homeostasis

Abstract: Roquin is an RNA-binding protein that prevents autoimmunity and inflammation via repression of bound target mRNAs such as inducible costimulator (Icos). When Roquin is absent or mutated (Roquinsan), Icos is overexpressed in T cells. Here we show that Roquin enhances Dicer-mediated processing of pre-miR-146a. Roquin also directly binds Argonaute2, a central component of the RNA-induced silencing complex, and miR-146a, a microRNA that targets Icos mRNA. In the absence of functional Roquin, miR-146a accumulates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 53 publications
(79 reference statements)
3
90
0
Order By: Relevance
“…Although, to the best of our knowledge, the regulatory mechanisms controlling miRNA-processing in the β-cell have not so far been investigated, several miRNAs with a role in β-cell identity are regulated at the pri/pre-miRNA processing level in other cell types. Examples are the already mentioned miR-7 (see above), miR-34a (Doridot et al, 2014; Herbert et al, 2014) or miR-146a (Srivastava et al, 2015). …”
Section: Perspectives For Future Studymentioning
confidence: 99%
“…Although, to the best of our knowledge, the regulatory mechanisms controlling miRNA-processing in the β-cell have not so far been investigated, several miRNAs with a role in β-cell identity are regulated at the pri/pre-miRNA processing level in other cell types. Examples are the already mentioned miR-7 (see above), miR-34a (Doridot et al, 2014; Herbert et al, 2014) or miR-146a (Srivastava et al, 2015). …”
Section: Perspectives For Future Studymentioning
confidence: 99%
“…A defect in the regulation of the transcript levels of ICOS, as a result of a mutation in the RNA-binding protein Roquin, is the main mechanism responsible for the autoimmune features of San/San mice in which T cells are responsible for driving the formation of high levels of GC B cells and ANA-producing cells (28,29). Pratama et al (30) shed new light on the role of miR-146a in the downstream regulation of ICOS expression on T cell subsets, including T FH and GC B cells.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype in Sanroque mice is dependent on a mutation in the RNA-binding protein Roquin. It was later shown that Roquin, through interaction with miR-146a, regulates the expression of ICOS and the expansion of T FH cells (29,30). The increase in the number of T FH cells correlates with high levels of autoantibody and disease activity in Sanroque animals.…”
mentioning
confidence: 99%
“…First, Roquins directly bind the 3′ untranslated region (UTR) of Icos mRNA and promote its decay through the Ccr4-Caf1-Not deadenylation complex and the Rck/Edc4/Dcp1a decapping complex (2,3,5,6,7). In addition, Roquins can bind Ago2 and downregulate the levels of miR-146a while simultaneously targeting Icos mRNA through a target-mediated microRNA decay (TMMD) (8). Augmented Icos expression appears sufficient to stimulate phosphoinositide 3-kinase (PI3K) signaling, phosphatidylinositol 3,4,5-tris-phosphate (PIP3) production and Akt-mediated inactivation of Forkhead Box O1 (Foxo1), a transcription factor required for T-cell suppression, by promoting its export from the nucleus to the cytoplasm (9,10).…”
mentioning
confidence: 99%
“…The ROQ domain is a winged-helix fold that mediates Roquin’s binding to its target mRNAs (14,15,16) together with flanking higher eukaryotes and prokaryotes nucleotide-binding (HEPN) domains (8). The C-terminus recruits the Ccr4-Caf1-Not complex to the mRNA (11).…”
mentioning
confidence: 99%